Evaluation of biological control agents against sheath blight of rice in Tripura - M. DATTA, SUBRATA BISWAS* and (Indian Phytopathology, 2013)
Four isolates of Trichoderma viride (TV-01, TV-02, TV-03 and TV-04), one each of T. harzianum (TH-01) and Pseudomonas fluorescens (PF-01) were evaluated against sheath blight disease of rice grown under upland condition in Tripura. Only Pseudomonas fluorescens, when applied both in soil as a supplement along with FYM and on foliage as spray (5% solution of 2 Ã—109 cfu), were effective in minimizing the disease. In poisoned food technique using cell-free culture filtrates, P. fluorescens showed maximum inhibition (56.3%) of radial growth of mycelium of Rhizoctonia solani. Significant inhibition of mycelial growth was also observed with the two isolates of T. viride (TV-01 & TV-04), while, other Trichoderma isolates were not effective both at 5ppm and 25ppm concentrations. The antagonistic effects of T. viride isolates were further confirmed in dual culture technique. In that case both hyperparasitization and antibiosis effects were observed with the effective T. viride isolates. The scerotial parasitisation as evident on the growth of green spore masses of T. viride (TV- 04) on sclerotia of R. solani after 14 days of growth in dual culture is found to be a very effective tool to minimize the over wintering inocula of the disease causing organism. Further, the present findings suggest that culture filtrates of T. viride or of P. fluorescens could be used as foliar spray for the management of the disease in the field.